Very late antigen integrins are involved in the adhesive interaction of lymphoid cells to human gingival fibroblasts. - Murakami, S (1993)
To date, it is still unclear how the trafficking and retention of activated lymphocytes in periodontal lesions are regulated. In this study, we investigated the molecular basis for the adhesive interactions between lymphocytes and human gingival fibroblasts (HGF). Peripheral blood T lymphocytes (PBT) exhibited binding ability, but only when the calls were activated with phorbol 12-myristate 13-acetate (PMA). Among several human cell lines tested, PMA-stimulated Molt-4, a human T-cell leukaemia line, also displayed significant binding ability to HGF. In order to clarify the molecule(s) involved in this cell-cell interaction, a panel of monoclonal antibodies (mAb) was prepared to PMA-activated Molt-4 and one clone, 4-145, was selected on the basis of its ability to block the binding of PMA-activated Molt-4 to HGF. Moreover, 4-145 inhibited the binding of not only activated Molt-4 but also activated PBT and other cell types to HGF. Biochemical and flow cytometric analyses revealed that 4-145 probably recognizes the beta 1 chain of very late antigen (VLA) integrins. Blocking experiments using mAb specific for the alpha-chain of VLA integrins demonstrated the involvement of alpha 4 (VLA-4) and, to a lesser extent, alpha 5 (VLA-5) chains in the adhesive interactions between T cells and HGF. Despite the significant involvement of VLA integrins in the adhesive interaction between PBT and HGF, the binding of PBT to human dermal fibroblasts (HDF) was not abrogated by 4-145, suggesting that HGF and HDF differ in their requirement of VLA integrins for adhesion to activated PBT. Furthermore, the fact that vascular cell adhesion molecule-1 (VCAM-1), one of the ligands of VLA-4, was not detected on HGF by flow cytometry and anti-fibronectin (FN) Ab did not block the adhesive interaction to HGF suggests that not-yet-identified ligand(s) for VLA-4 might be present on HGF.